2013
DOI: 10.1200/jco.2012.45.3571
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Survival in Patients With BRCA1-Negative and BRCA1-Positive Breast Cancer

Abstract: The 10-year survival rate among women with breast cancer and a BRCA1 mutation is similar to that of patients without a BRCA1 mutation. Among women with a BRCA1 mutation, survival was much improved after oophorectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 20 publications
9
85
2
5
Order By: Relevance
“…Impact of oophorectomy on mortality results in large part from reduction in the incidence of ovarian, tubal, and peritoneal cancers-but there is an important component from reducing breast cancer incidence and and once the cancer is diagnosed, it reduces patient case fatality by 70%. 8 Average age at cohort entry was 46.0 years, and women were observed until a mean age of 51.6 years. It is expected that in young women, noncancer causes of death will be rare, and reduction in all-cause mortality associated with oophorectomy may attenuate as the women age and other causes of death emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of oophorectomy on mortality results in large part from reduction in the incidence of ovarian, tubal, and peritoneal cancers-but there is an important component from reducing breast cancer incidence and and once the cancer is diagnosed, it reduces patient case fatality by 70%. 8 Average age at cohort entry was 46.0 years, and women were observed until a mean age of 51.6 years. It is expected that in young women, noncancer causes of death will be rare, and reduction in all-cause mortality associated with oophorectomy may attenuate as the women age and other causes of death emerge.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that oophorectomy is associated with improved survival in BRCA1 carriers treated for early-onset breast cancer. 35 It is important to establish whether the preservation of ovarian function in young women with breast cancer and a BRCA mutation has an adverse impact on disease recurrence.…”
Section: Proportion With Induced Amenorrheamentioning
confidence: 99%
“…In fact, in 1997, a randomized trial that enrolled 852 high-risk patients treated with combined CMF, chemotherapy, and radiation therapy, showed a 10-year OS rate of 54% (15). In 2013, another trial with 3,312 patients that did not carry BRCA1, were treated with anthracycline-taxane-based chemotherapy and showed a 10-year OS rate of 82.2% (16).…”
Section: Discussionmentioning
confidence: 99%